Climate-smart Cocoa: Adaptation Practices for Smallholder Systems in Ghana - Bunn, Christian; Lundy, Mark M.; Castro, Fabio (2016)
The presentation focused on results from farmer consultations on adequate climate smart practices. This presentation first highlighted the elaborate approach that was used to identify, assess and validate long lists of specific CSA practices for each of the climatic impact zones. Desk study, expert interviews and farmer consultations were followed up with field assessments, a stakeholder workshop of several days at CRIG and finally field verification with reaching over a thousand farmers in the three impact zones.